2019
DOI: 10.1007/s00268-019-05001-2
|View full text |Cite
|
Sign up to set email alerts
|

Video‐Assisted Thoracic Surgery (VATS) Talc Pleurodesis Versus Pleurectomy for Primary Spontaneous Pneumothorax: A Large Single‐Centre Study with No Conversion

Abstract: Background Primary spontaneous pneumothorax (PSP) is a relatively common clinical entity with high incidence in the young population. Video-Assisted Thoracic Surgery (VATS) bullectomy and chemical or mechanical pleurodesis are two primary modalities of treatment. There has been much debate on the ideal mode of pleurodesis, but the literature on surgical outcomes comparing VATS pleurectomy with talc pleurodesis has been inconclusive. Methods We performed a single-centre 5-year observational retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Although not reaching statistical significance, the larger volume of resected parietal pleura in the 3-P-VATS groups (14.3 vs. 12.8 cm 3 ), as well as the additional port access, may have contributed to the higher rate of hemothorax in the 3-P-VATS group. As described in previous studies, VATS with additional pleurectomy is associated with reduced recurrence rates [ 14 16 ]. However, the volume of pleurectomy seems to affect postoperative outcome in terms of complications and postoperative pain.…”
Section: Discussionmentioning
confidence: 75%
“…Although not reaching statistical significance, the larger volume of resected parietal pleura in the 3-P-VATS groups (14.3 vs. 12.8 cm 3 ), as well as the additional port access, may have contributed to the higher rate of hemothorax in the 3-P-VATS group. As described in previous studies, VATS with additional pleurectomy is associated with reduced recurrence rates [ 14 16 ]. However, the volume of pleurectomy seems to affect postoperative outcome in terms of complications and postoperative pain.…”
Section: Discussionmentioning
confidence: 75%
“…Nowadays, VATS–bullectomy with partial pleurectomy (VBPP) is a well-established and increasingly used surgical treatment for primary spontaneous pneumothorax (PSP). Recently, VBPP has been reported with superior performance and low rates of recurrence compared to VATS bullectomy alone [ 20 , 21 , 24 , 25 ]. However, only a few studies elucidate its effectiveness in terms of long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, VATS with bullectomy alone was demonstrated to have recurrence rates up to 20% [ 18 , 19 ]. When combined with pleurectomy, the short- and medium-term recurrence rates were reported to reduce to 1–6% [ 20 , 21 , 22 ]. For long-term results, only a few studies are described in the literature [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, VATS-bullectomy with partial pleurectomy (VBPP) is an increasingly used und well-established surgical technique for complicated spontaneous pneumothorax. In the treatment of primary spontaneous pneumothorax (PSP), VBPP has been well-reported to be effective and is associated with low rates of recurrence compared to VATS-apical pleurectomy, VATS-talc pleurodesis and bullectomy alone [ 15 , 16 , 17 , 18 ]. For treatment of SSP, reports on clinical outcomes and recurrence rates following VBPP are rare.…”
Section: Discussionmentioning
confidence: 99%